The 'obesity epidemic' : an analysis of representations of obesity in mainstream South African newspapers post-1997 - Malan, Chantelle Therese (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2015)
This study of 449 newspaper articles from South Africa from 1997 provides an analysis of the representations of obesity evinced in the corpus. The research argues that obesity is overwhelmingly framed as being diseased and that there are four main refrains within this frame, namely, statistics on obesity, the naturalisation of negative assumptions about fat, the social dysfunction of fat and the use of crisis metaphors to describe fatness. This framing lends itself to representations of obesity which are raced, gendered and classed. Fat bodies are portrayed as being in deficit and fat people as lacking agency. The disproportional focus on black bodies in the corpus can be attributed to assumptions of 'incivility' which are premised on racial stereotypes which construct black people as being unintelligent, irrational, lacking agency and being largely dependent on others to survive. This disproportional focus on black bodies can also be understood in the context of emerging markets. This study argues that the medicalisation of obesity has contributed to many oversimplifications and contradictions in the representation of obesity in the corpus, which seem to go unquestioned, such as the conflation of weight and health, something I argue is one of the main contributors to the negative consequences of the dominant framing of obesity. Framing obesity as medicalised also promotes fat shaming and acts as a form of social control which maintains existing power relations through the use of discursive practices for the identification and control of deviants. These representations are problematic chiefly because they promote the dehumanisation of fat people, but also because that they do not promote good health as they claim to do.
Keywords: Obesity -- South Africa; Obesity -- Press coverage -- South Africa; Obesity -- Social aspects -- South Africa; Discrimination against overweight persons -- South Africa; Social medicine -- South Africa; Agent (Philosophy); Social control -- South Africa